HISTORY OF EDUCATION IN THE COUNTRIES OF THE WORLD (American Journal of Pedagogical and Educational Research, 2025)
This article discusses the emergence of educational systems in countries around the world, the first pedagogical views. Special attention is also paid to the specific features of European education, new reforms, opportunities, achievements, and a comparative analysis of the European education system.